Зміни вмісту вільного проліну у рослинах озимої пшениці протягом осінньо-зимового періоду - Майор, П.С.; Захарова, В.П.; Великожон, Л.Г. (Физиология и биохимия культурных растений, 2009)
Досліджували динаміку змін вмісту вільного проліну у листках озимої пшениці різних генотипів протягом осінньо-зимового періоду в умовах вегетаційного та дрібноділянкового дослідів. Виявлено, що зниження температури до мінусових значень викликало швидку втрату води листками рослин, тоді як зростання вмісту проліну у них відбувалось із деякою затримкою у часі лише за умови підвищення температури до низьких плюсових значень. Отримані дані свідчать як про опосередкований (через зневоднення тканин, спричинене морозом), так і про можливий прямий вплив низьких температур на накопичення цієї амінокислоти у рослинах озимої пшениці. Исследовали динамику изменений свободного пролина в листьях озимой пшеницы разных генотипов в течение осенне-зимнего периода в условиях вегетационного и мелкоделяночного опытов. Обнаружено, что снижение температуры до минусовых значений вызывало быструю потерю воды листьями растений, тогда как увеличение содержания пролина в них происходило с некоторой задержкой во времени лишь при условии повышения температуры до низких плюсовых значений. Полученные данные свидетельствуют как об опосредованном (вследствие обезвоживания тканей, вызванного морозом), так и о возможном прямом влиянии низких температур на накопление этой аминокислоты в растениях пшеницы. The contents of free proline and the proportion of dry matter in plants of winter wheat (Triticum aestivum L.) were studied in the vegetation and small plot field experiments under natural temperature conditions during autumn-winter periods of three years. It was found that the lowering of the temperature to negative values caused a rapid loss of water in leaves of plants, while the increase of proline content occurred with some time delay only when the temperature had risen to low positive values. The amplitude of variation of proline content in leaves of vegetation experiment in comparison with small plot field one were generally higher due to greater influence of the temperature factor on plants. Under a snow cover, the increase in the proportion of dry matter in leaves under the action of frost was weaker than the increase in proline content. The data show both the indirect (through dehydration of tissues caused by frost) and possible direct effect of low temperatures on the accumulation of this amino acid in wheat plants.